Readiness for Online Learning among Social Studies Students During the Pandemic - Juspher G. Handang (Researchparks Publishing, 2022)
This Study is an attempt to measure the level of Readiness in Online Learning of Social Studies Students. Using the Student Readiness for Online Learning (SROL) Instrument developed by Florence Martin, Brandy Stamper, and Claudia Flowers. This study reports the level of Readiness of Social Studies Students from various universities in the Philippines, through the category of importance and confidence in the competencies the respondents possess as the basis of their Online Learning Readiness. The level of readiness was also measured in terms of the Respondents’ Gender. In addition, data were statistically analyzed using descriptive statistics. Result presented that Social Studies Students has a High Level of Readiness in both confidence and importance category. In terms of Gender there were no significant differences between the Male and Female Respondents.